The Problem of Duopoly Reconsidered - Coase, R. H. (Review of Economic Studies, 1935)
Journal Article The Problem of Duopoly Reconsidered Get access R. H. Coase R. H. Coase Liverpool Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 2, Issue 2, February 1935, Pages 137–143, https://doi.org/10.2307/2967560 Published: 01 February 1935